Innovation In Orang Ulu Indigenous Crafts - Faridah, Sahari; Rahah, Hj Hasan (Institute of Borneo Studies, UNIMAS, 2016)
The rapid depletion of raw materials in Belaga, Sarawak due to extensive timber extraction, land clearing for oil palm plantation and inundation of river valleys for hydroelectric power dam construction as well as changing lifestyle and values; consequences of development have affected the production of Orang Ulu rich material culture such as mats, baskets and other utilitarian items sustainable. Arrays of new emergence of Orang Ulu material culture assemblage reflects forms of their adaptation to a dynamic change in culture dictated by the scarcity of raw materials, global taste and acceptance of readily commercialized materials. Although it requires new knowledge and skills in the new reproduction; that is the way their rich material culture can survive. This paper discusses the innovation in the Orang Ulu indigenous material through the introduction of plastic as an alternative material used in traditional crafts and utilitarian objects reproduction; and its implication on values and authenticity of the new reproduction to the indigenous culture as a whole.